PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN GEOGEBRA CLASSROOM PADA MATERI DIMENSI TIGA UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Nella Dwi Putri (Departemen Matematika, 2021)
Several studies show that students' understanding of mathematical concepts in three-dimensional material is still low. One of the reasons is that the visualization on the LKPD used is still lacking so that students cannot easily explore three-dimensional material. Therefore, LKPD was developed using GeoGebra Classroom on three-dimensional material, which is expected to facilitate students' understanding of mathematical concepts. This research is categorized as research and development using the Plomp model which consists of three stages. At the initial investigation stage (preliminary research) needs analysis, curriculum analysis, concept analysis, and student analysis are carried out. At the prototype stage (prototyping stage), a formative evaluation is carried out in which each evaluation is revised until a prototype 4. Then the LKPD using the geogebra classroom is declared valid with an average validity value obtained of 90.1% with very valid criteria. In addition, LKPD is also declared practical with an average practicality value obtained from students of 94.09% and educators of 89.18% with very practical criteria. Keywords - LKPD, understanding of mathematical concepts, geogebra classroom, valid, practical.